2013
DOI: 10.1186/1471-2253-13-18
|View full text |Cite
|
Sign up to set email alerts
|

Absence of neurotoxicity with perineural injection of ultrasound gels: assessment using an animal model

Abstract: BackgroundUltrasound gels may contain propylene glycol and glycerol, which are neurotoxic in high concentrations. If the needle passes through gel during regional anesthesia, gel may be injected near the nerve. It is unknown if this practice poses a risk for neurotoxicity. Using an animal model, we assessed the histological changes of perineural propylene glycol on nerves. We then assessed three commonly used sterile gels for evidence of neurotoxicity.MethodsMicro-ultrasound guided perineural sciatic nerve inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, application to the peripheral nerve is limited, although ultrasonography-guided nerve stimulation is frequently used for regional anesthesia (Wadhwa et al 2011). Recently, ultrasonography-guided injection has facilitated the safe delivery into the perineural region (Belavy et al 2013), demonstrating the safety of ultrasonography gels and needle injection. There was a minimal inflammatory response and no damage to the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…However, application to the peripheral nerve is limited, although ultrasonography-guided nerve stimulation is frequently used for regional anesthesia (Wadhwa et al 2011). Recently, ultrasonography-guided injection has facilitated the safe delivery into the perineural region (Belavy et al 2013), demonstrating the safety of ultrasonography gels and needle injection. There was a minimal inflammatory response and no damage to the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mixed gel was suitable for pleural marking. A sterilized echogenic jelly is said not to cause tissue degeneration during subcutaneous insertion (14) and is guaranteed to be safe as a material used for marking. Additionally, shielding by the surgical tape may make it safer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported signs of chronic inflammation, such as adhesions, fascia thickening, vascular changes, and scar tissue formation that cause compression neuropathy in PNB [156]. Such inflammation can also be caused by accidental injection of ultrasound gel [157][158][159] or alcohol-based disinfectant (used for surface disinfection) around the nerve during PNB. Neuropathy caused due to inflammation following surgery is called postsurgical inflammatory neuropathy (PSIN).…”
Section: Inflammatory Mechanismmentioning
confidence: 99%